(untitled) (Journal of the College of Basic Education, 2023)
The aim of the research is to identify the intellectual diversity in the design of artistic works and their relationship to the creative abilities of art education students. The research community consisted of (10) plastic artworks, and (3) artworks were selected as a sample for analysis. The researcher used the descriptive approach (content analysis method). It fits with the goal of the research, and the research tool was prepared as it consisted of an analysis form, and the researcher used the statistical methods: Cooper’s equation to find the percentage of agreement between the arbitrators, Scott’s equation to calculate the validity of the tool, and Pearson correlation coefficient to extract the stability by the split-half method. As for the most important results: the secondary items appeared (designing technical elements, techniques, using materials). Strongly associated with the main paragraph of intellectual diversity, where the formations of artistic forms of civilization and heritage were considered as authentic folk art characterized by the inherited environmental beauty. As for the most important conclusions: The intellectual diversity of artistic works, with the diversity of the basic elements in the implementation of artworks on different materials, adds to the works an artistic aesthetic through the consistency of the design form with the volume and function of the completed work